Pelatihan Pengembangan Media Pembelajaran Berbasis Digital di SMK Muhammadiyah 2 Playen, Gunungkidul - Purnama, Dian Normalitasari; Purnamasari, Niken; Hidayah, Nurul (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of digital technology requires teachers to be more innovative in designing interactive and contextual learning that aligns with the characteristics of 21st-century learners. However, observations revealed that teachers at SMK Muhammadiyah 2 Playen still face challenges in utilizing digital media, both in terms of technical competence and pedagogical integration. This Community Service Program (PkM) aimed to enhance teachers’ competence in developing digital-based learning media through training and mentoring. The methods employed included lectures, discussions, demonstrations, and hands-on practice, covering materials such as the introduction of digital media concepts, the use of applications (Canva for Education, Liveworksheet, and interactive PowerPoint), as well as the design of contextual media according to subject areas. The program was conducted in three sessions from August to September 2025, involving 37 teachers as participants. Evaluation results showed that all participants (100%) attended the program, 95% rated the quality of materials as excellent, and 80% reported significant improvement in their digital media development skills. The media products created demonstrated creativity and relevance to learning in the Merdeka Curriculum. Thus, this program successfully improved teachers’ competence while also supporting the digital transformation of education at SMK. It is expected that the program can be replicated in other schools with extended training duration and continuous mentoring to achieve more optimal results.